Aquatic invertebrate communities in tank bromeliads: how well do classic ecological patterns apply? - Jocque, Merlijn; Field, Richard (Springer, 2014)
Tank bromeliads (Bromeliaceae) often occur in high densities in the Neotropics and represent a key freshwater habitat in montane forests, housing quite complex invertebrate communities. We tested the extent to which there are species richness–altitude, richness–environment, richness–size, richness–habitat complexity and richness–isolation relationships for the aquatic invertebrate communities from 157 bromeliads in Cusuco National Park, Honduras. We found that invertebrate species richness and abundance correlated most strongly, and positively, with habitat size, which accounted for about a third of the variance in both. Apart from bromeliad size (equivalent of the species– area relationship), we found remarkably little evidence of classic biogeographic and ecological relationships with species richness in this system. Community composition correlated with altitude, bromeliad size and position, though less than 20% of the variation was accounted for by the tested variables. The turnover component of dissimilarity between the communities correlated with altitude, while the nestedness-resultant component was related to bromeliad size. The unexplained variance could reflect a large stochastic component in the system, associated with the ephemerality of the habitat patches (both the plants themselves and the fluctuations in their water content) and stochasticity due to the dispersal dynamics in the system. We conclude that there is a small contribution of classic biogeographic factors to the diversity and community composition of aquatic invertebrates communities in bromeliads. This may be due to the highly dynamic nature of this system, with small patch sizes and high emigration rates. The patterns may mostly be driven by factors affecting colonisation success.